Interconnected Failures: An Ecological Systems Analysis of Wrongful Convictions in the U.S. Criminal Justice System - Dr. Marcus D. Hollowell; Dr. Alicia N. Rosario (International Journal of Law And Criminology, 2025)
This study applies an ecological systems theory framework to examine the complex, interconnected factors contributing to wrongful convictions in the U.S. criminal justice system. Moving beyond isolated explanations, the analysis considers multiple systemic levels—including individual, institutional, community, and societal influences—that interact to produce judicial errors. Key elements such as police misconduct, prosecutorial overreach, inadequate defense, systemic bias, and sociopolitical pressures are explored as part of a broader ecosystem of failure. By situating wrongful convictions within this multidimensional context, the study highlights the need for holistic reform strategies that address the structural and cultural dynamics underpinning miscarriages of justice.